Theorizing Foreign Policy in a Globalized World - Hellmann, Gunther; Jørgensen, Knud Erik.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
In this collection of refreshing and provocative essays, the contributors to Theorizing Foreign Policy in a Globalized World reflect on the game-changing political impact of globalization, outlining the situation as it currently stands and suggesting strategies for analyzing foreign policy and global governance.
Keywords: International relations; Globalization; Diplomacy; Comparative politics; Political science; International Relations; Globalization; Diplomacy; Comparative Politics; Political Science; Foreign Policy